Design and Development of Industry 4.0 Smart Lean Kaizen Manufacturing: A Case Study on Extrusion Line of Vacuum Hose - Afiq Durrani Azli; Falah Abu; Mohd Hazri Mohd Rusli; Joshua Goh; Goh Wai Kah; Mah Lai Ching; Noor Azlina Mohd Salleh (International Journal of Integrated Engineering, 2024)
This article investigates a manufacturing company’s extrusion process in demonstrating the value-added benefits of Lean Kaizen Approaches through autonomation (jidoka) and adoption of Industry 4.0 technologies. The scope of study focuses on the extrusion process line of a vacuum hose as the pilot study area. This study proposes using Lean Kaizen Approaches, SolidWorks, Arduino and IR4.0 sensors in designing, developing and adopting a four-phase framework for Lean Kaizen continuous improvement from sampling and manual weighing to an automated real time weighing and segregation system of good and out of specification vacuum hose product. The findings showed that with full financial and non-financial support from top management and the whole organization’s willingness to transform the company to Smart Manufacturing, the automated unmanned weighing and separation system have been able to achieve the company’s intended target in using no manpower to weigh the hose and has a real time monitoring system of all vacuum hoses extruded. This study has contributed to the company by improving their extrusion line operations using an unmanned operator for the weighing system as well as collecting data on vacuum hose weight and length in real time. By incorporating Lean Kaizen Approaches and Industry 4.0 technologies, the company enhanced operational efficiency through automated weighing and separation system, manpower reduction and provide greater customer satisfaction as it is guaranteed that all vacuum hose weight and length meet the required specifications. Further research is needed to explore the applicability of the proposed approaches in different manufacturing and Industry 4.0 contexts to investigate additional factors influencing the successful implementation of Smart Manufacturing.